Drug-induced autoimmune hepatitis associated with turmeric dietary supplement use. (10th September 2018) - Lukefahr, Ashley L; McEvoy, Sean; Alfafara, Chelsea; Funk, Janet L
Abstract : Turmeric dietary supplement sales, which accounted for US69 million in spending in 2016, have been increasing exponentially in the USA, making this one of the most popular botanical supplements sold in the USA. Herbal supplement use, which is generally regarded as safe by consumers, is not usually reported to healthcare providers. We reported here on a case of autoimmune hepatitis, occurring in a 71-year-old woman taking turmeric dietary supplements for the maintenance of cardiovascular health, which resolved rapidly following discontinuation of the turmeric supplements. Of particular note, turmeric use was not documented in the patient's medical records and the potential causative role of the turmeric supplementation was ultimately identified by the patient rather than the healthcare providers. To our knowledge, this is the first documented report of turmeric supplement-induced autoimmune hepatitis.